Process analysis for deep drawing of tailored heat treated blanks - Kerausch, Michael; Merklein, Marion (Proceedings of the 8th International Conference on Technology of Plasticity (ICTP), 09.-13.10., Verona, Italy, 2005)
This paper will summarize the results of a development to improve the forming performance of hardenable aluminum alloys in deep drawing processes. Experimental investigations show the feasibility to change the mechanical properties with a laser heat treatment by influencing the precipitation structure. This enables to manufacture so called Tailored Heat Treated Blanks (THTB) by a local heat treatment. Introducing mechanical property gradients improves the drawing capabilities of THTB significantly relative to homogenous blanks in the naturally aged condition T4. In case that the deformation zone is softened, the maximum drawing force is reduced, while the force transferring area is not affected by the selective heat treatment. Accordingly the total process energy for drawing THTB is lower in comparison to the conventional deep drawing process. As a result the probability of bottom fracture is reduced and a higher drawing ratio can be attained.
LFT Import::2019-08-05 (1220)